Effects of extrusion variables on extrudate characteristics from corn-based enriched with soybean residue - K Unsaeng; P Hannanta-anan; M Phongpipatpong (My University, 2019)
Abstract Soybean residue is a food processing by-product of soya milk or tofu production process. It consists of rich protein and fiber. As a result, reprocessing soybean residue as human food can be a worthwhile alternative. This research focuses on studying the effects of extrusion process and the extrudate characteristics. The mixture of corn grit and soybean residue flour was extruded by single-screw extruder to produce high protein snack. Experimental design was performed by Box-Behnken design and Response surface methodology (RSM) was used to assess the effects on extrusion variables, including screw speed (370-430 RPM), soybean residue flour content (20-40%) and feed moisture (14-18%) on the properties of the extrudates including, expansion ratio (ER), density (D), water absorption index (WAI), water solubility index (WSI) and hardness (H). Analysis of variance showed that the most significant variables are soybean residue, which has negative effect on ER and positive effect on H, and screw speed, which has positive effect on ER and H, while feed moisture is non-significant in most characteristics.
Keywords: Die swell; Residue (chemistry); Extrusion cooking; Food composition and properties